Hydraulics Performance of SDMS-350-8 Single-multistage CentrifugalExtractor with High Flux for Nuclear Applications - XING Yuntong, YANG Xinwei, CHEN Yong, WANG Bo (Yuanzineng kexue jishu)
Reprocessing of nuclear fuel to achieve closed nuclear fuel cycle can effectively improve the utilization efficiency of nuclear fuel. At present, the nuclear fuel reprocessing process that has been realized engineering application is to separate different metal ions by using different partition coefficients of metal ions in extractants. Therefore, extraction equipment is the key core equipment in the field of nuclear fuel reprocessing. The centrifugal extractor has the advantages of high mass transfer efficiency and low hydraulic retention time, but the existing single-stage centrifugal extractor usually occupies a large area, which leads to expensive plant construction costs. In order to meet the throughput requirement of the reprocessing plant under the premise of minimizing the plant area, in this study, a high flux SDMS-350-8 multistage centrifugal extractor with a drum diameter of 350 mm and a total number of stages of 8 was designed and manufactured, which can realize multistage centrifugal extraction in a single device. Based on the engineering application conditions, the hydraulic performance experiments were carried out with HNO3 aqueous solution and 30% TBP-kerosene. The effects of the drum rotating speed, heavy phase weir plate semidiameter and mixing paddle size on the hydraulic performance of SDMS-350-8 multistage centrifugal extractor were studied. The results show that the suitable drum rotating speed range of SDMS-350-8 centrifugal extractor is 1 400-1 600 r/min, when it is lower than 1 400 r/min, it is difficult to establish a stable hydraulic operation state under the required flow ratio (200/800). With the increase of drum rotating speed, the two-phase entrainment will gradually increase. The effects of heavy phase weir plate semidiameter and flow ratio on the maximum treatment flux of SDMS-350-8 centrifugal extractor were studied. In addition, it is found that different aqueous phase weir plate semidiameters are suitable for different flow ratios. The aqueous phase weir plate with 113 mm semidiameter is suitable for the flow ratios of 1/5-1/3, the aqueous phase weir plate with 110 mm semidiameter is suitable for the flow ratios of 1/1-2.5/1, and the aqueous phase weir plate with 107.5 mm semidiameter is suitable for the flow ratio of 5/1. The size of the mixing paddle was also optimized. The results show that by increasing the size of mixing paddle from 118 mm to 122 mm, the maximum treatment flux increases to 1 600 L/h. The above results show that the SDMS-350-8 multistage centrifugal extractor has the advantages of large treatment flux, wide operation range and good hydraulic performance, and has the potential to be applied in nuclear engineering.